Penerapan Akuntansi Berkelanjutan (Sustainability Accounting) untuk UMKM Ramah Lingkungan di Kelurahan Benda Baru, Kota Tangerang Selatan - Tyas Andini Cinthya Dewi; Wasniyah W; Ajeng Rahmawati Aprilia Mellayantie; Irma Wati; Rika Kartikasari; Sugiyanto S; Suripto S (Yayasan Daarul Huda Kruengmane, 2025)
The development of micro, small, and medium enterprises (MSMEs) oriented toward environmental sustainability has become a strategic necessity in responding to current economic and ecological pressures. This Community Service Program (PKM) aims to enhance the understanding of sustainability accounting among environmentally friendly MSMEs in Benda Baru Subdistrict, South Tangerang City, and to evaluate its impact on resource management, cost efficiency, and business reputation. The research method employed is a case study with a qualitative approach through in-depth interviews and field observations. The results indicate that the implementation of sustainability accounting increases MSME actors’ awareness of waste management, efficient energy use, and the recording of environmental costs, thereby contributing simultaneously to economic and environmental performance. These findings provide practical implications for policymakers and MSME practitioners in promoting responsible and sustainable business practices.